Evaluasi User Experience Sistem Informasi Akademik Pada Website mahasiswa.pkkb.ac.id Menggunakan User Experience Questionnaire (UEQ) - Agus Ariwanta, I Putu Yesha; Gunawan, I Made Agus Oka; Indrawan, Gede (Journal of Information System Research (JOSH), 2024)
The information system website on mahasiswa.pkkb.ac.id is a crucial platform for students to access academic information, class schedules, and other educational resources. Evaluating the User Experience (UX) of such a website's information system is a critical step in enhancing the quality of online educational services. In this research, the researcher utilized the User Experience Questionnaire (UEQ) method to measure the UX on the mahasiswa.pkkb.ac.id student information website. The research was conducted at Kartini Bali Health Polytechnic with 63 student respondents who are currently active academically. The results of evaluating user experience using the UEQ method for each aspect are evaluated as follows: 4,444 attractiveness points are rated 1,513, clarity is rated 1,341, effectiveness is rated 1,488, reliability is rated 1,488 was rated 1,409, stimulation was rated 1,552 and novelty was rated 1,115. This shows that all aspects of the value user experience received positive ratings. The outcomes of this study demonstrate that the User Experience Questionnaire (UEQ) is an effective method for assessing and measuring the User Experience (UX) of the mahasiswa.pkkb.ac.id student information website, and the resulting improvement recommendations can serve as the foundation for future developments in enhancing online educational services.